Measuring Teacher Personality Competence: Era 5.0 Challenges for Teachers in Indonesian Archipelago - Wakano, Abidin; Latuapo, Ridwhan; Lapele, Fitria; Prihono, Eko Wahyunanto (AL-ISHLAH: Jurnal Pendidikan, 2024)
Teachers in archipelagic regions face challenges such as limited access, geographical isolation, and cultural diversity, particularly in the Society 5.0 era. This study aims to assess the feasibility of an instrument for measuring teacher personality competency in this context. Using a quantitative approach, the study was conducted in Maluku Province, with a multistage random sample of 752 teachers from 94 schools. The instrument employed a modified four-point Likert scale, and data analysis was conducted using the PLS-SEM method to evaluate the measurement and structural models. Key findings include: 1) Exploratory Factor Analysis (EFA) identified six dominant factors and 29 items to measure teacher personality competency; 2) The measurement model demonstrated feasibility, with construct validity confirmed through convergent validity (loading factors 0.70 and Average Variance Extracted 0.50) and discriminant validity (Fornell-Larcker criterion and Heterotrait-Monotrait Ratio 0.90). Reliability was supported by Cronbach’s Alpha, Rho_A, and composite reliability values all exceeding 0.70. These results indicate that the instrument is suitable for assessing teacher personality competency in island regions, helping address the challenges of the Society 5.0 era. The study has important implications for Indonesian education stakeholders, providing a validated tool to guide teacher performance evaluations.